Harmonization of Asset Valuation Laws in ASEAN Member States: A Comparative Legal Analysis of Regulatory Divergence and Convergence - Le Thi Thao (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2026)
This article examines the challenges of harmonizing asset valuation laws across ASEAN member states amid increasing regional economic integration. Despite the establishment of the ASEAN Economic Community, regulatory fragmentation in asset valuation continues to create legal uncertainty for cross-border transactions. This study assesses whether legal harmonization in asset valuation within ASEAN is necessary and practically achievable by adopting a comparative doctrinal legal methodology, analyzing statutory frameworks and regulatory practices in selected ASEAN jurisdictions, including Singapore, Vietnam, and Indonesia. The analysis focuses on three dimensions: valuation standards, regulatory governance, and enforcement mechanisms. The findings reveal significant divergences across member states, particularly in the absence of unified valuation standards, varying institutional capacities, and inconsistent regulatory enforcement. These challenges hinder effective legal harmonization and limit the efficiency of regional financial integration. The article argues that a hybrid harmonization model—combining regional soft-law coordination with gradual domestic legal alignment—offers a more feasible pathway for ASEAN. This approach provides practical policy implications for strengthening regulatory coordination, enhancing legal certainty, and facilitating cross-border transactions. This study contributes to the literature by reframing asset valuation not merely as a technical issue but as a core regulatory challenge in ASEAN legal integration.